Analisis Semiotik Puisi “Kematian Dan Makam Mistik” Karya Jalaluddin Rumi (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This research was motivated by the author's admiration for Maulana Jalaluddin Rumi's work and the author's interest in analyzing one of the poems as extraordinary material because there are many meanings and implied signs that need to be studied for meaning. The purpose of this study is to examine meaningfulness based on signs contained in one of Jalaluddin Rumi's poems entitled "Death and the Mystical Tomb" using a semiotic approach. The semiotic approach is an approach by examining literary works based on their signs, these signs represent other things, not actual things. Therefore, the semiotic approach in poetry will clarify the meaning that has been a sign in the expression of a poet. . The research method used in this study is a qualitative descriptive method, which is a method that explains and describes the results of poetry analysis based on the data obtained. This study focuses on the discussion of the marks that appear in the poem "Death and the Mystical Tomb" by Jalaluddin Rumi which is then analyzed, so as to show signs that represent the meaning of the poem. The poem entitled "Death and the Mystical Tomb" by Jalaluddin Rumi is closely related to self-awareness of love for God. In the poem it can be concluded that there are many meanings implied through signs and signs in the form of symbols and icons only, which in its meaning leads to the existence of God's love which manifests in the beauty of the heart as a sign of life.